2014
DOI: 10.1158/0008-5472.can-13-3195
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing of Asian Lung Cancers: Second-Hand Smoke Unlikely to Be Responsible for Higher Incidence of Lung Cancer among Asian Never-Smokers

Abstract: Asian nonsmoking populations have a higher incidence of lung cancer compared with their European counterparts. There is a long-standing hypothesis that the increase of lung cancer in Asian never-smokers is due to environmental factors such as second-hand smoke. We analyzed whole-genome sequencing of 30 Asian lung cancers. Unsupervised clustering of mutational signatures separated the patients into two categories of either all the never-smokers or all the smokers or ex-smokers. In addition, nearly one third of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 41 publications
6
29
0
Order By: Relevance
“…Earlier studies have demonstrated that LUADs of East Asians exhibit disparate mutational spectra (e.g. more prevalent activating mutations in EGFR ) relative to LUADs from Western (or Caucasian) patients [48,49]. It is reasonable to surmise that mutational differences in AAHs, across patients of different ethnicities, to roughly reflect those we observe in LUADs.…”
Section: Discussionsupporting
confidence: 60%
“…Earlier studies have demonstrated that LUADs of East Asians exhibit disparate mutational spectra (e.g. more prevalent activating mutations in EGFR ) relative to LUADs from Western (or Caucasian) patients [48,49]. It is reasonable to surmise that mutational differences in AAHs, across patients of different ethnicities, to roughly reflect those we observe in LUADs.…”
Section: Discussionsupporting
confidence: 60%
“…This actually constitutes one of the possible reasons why mutation spectrum is not affected by indirect smoking exposure. These findings are in line with recent observations obtained by whole-genome sequencing [27]. Thus, some other risk factor may be suspected in this setting, such as environmental pollution (including natural radon and atmospheric pollution), occupational exposure, domestic pollution (cooking and heating fumes, or cooking oil), personal history of cancer or respiratory disease, or familial history of cancer supporting the role of genetic factors [2].…”
Section: Discussionsupporting
confidence: 91%
“…21 However, the increase in lung cancer incidence in never-smokers is a very controversial issue, with proposed explanations principally being secondhand smoke, other environmental toxins, and genetic polymorphism. 23,24 Moreover, as the proportion of elderly patients increases, aging becomes a risk factor per se, with smoking being degraded as a factor. 25 Histological distribution showed an increase in adenocarcinoma rather than squamous cell carcinoma frequency over time.…”
Section: Discussionmentioning
confidence: 99%